Original Research Parental experiences of stillbirth rituals in Limpopo, South Africa - Lunghile Shivambo; Dumile Gumede (Health SA Gesondheid: Journal of Interdisciplinary Health Sciences, 2025)
Background: Stillbirth remains a significant global health issue. Although extensive literature exists on burial practices for live births, there is a notable gap in evidence regarding the specific cultural practices related to the burial of stillborn infants.